Multifaceted Interpretations of ‘ağā’ib (Miraculous): On the Example of the Work Risāla al-Intiṣār li Qidwa al-’Aḫyār by Ali-Dede Bošnjak (Prilozi za orijentalnu filologiju, 2017)
This paper presents the manuscript Risāla al-intiṣār li qidwa al-’aḫyār of the famous Bosnian philosopher and travelogue writer Ali-dede Bošnjak which, by its contents, belongs to the so-called ‘ağā’ib literature. The paper points to the former interpretations of the similar textual corpora; however, it tries to present its alternative interpretations as well. In line with the new interpretation of ‘ağā’ib literature, the descriptions in the Epistle are observed in the comparison to certain parts of the basic text of Islamic culture, namely, to specific ayats from the Qur’an, which certainly served as an inspiration to the author during the composition of the Epistle.